The Changes of Twist1 Pathway in Pulmonary Microvascular Permeability in a Newborn Rat Model of Hyperoxia-Induced Acute Lung Injury - Ying Ruan; Wenbin Dong; Lan Kang; Xiaoping Lei; Rong Zhang; Fan Wang; Xiaodan Zhu (Frontiers Media S.A., 2020)
Background: Bronchopulmonary dysplasia (BPD) is a chronic lung disease in preterm infants, which is characterized by alveolar and vascular dysplasia and increased vascular permeability. Hyperoxia is a critical factor in the pathogenesis of BPD, hyperoxia-induced acute lung injury (HALI) model has similar pathological manifestations as human BPD, therefore, may provide insight into the pathogenesis of human BPD. Studies have shown that Twist1 regulates pulmonary vascular permeability of LPS-induced lung injury through the Ang-Tie2 pathway. However, the effect of Twist1 pathway on vascular permeability in HALI has not been reported.Methods: We randomly exposed newborn rats to the room air or hyperoxia for 14 days. Lung histopathology, immunofluorescence, vascular permeability, mRNA and protein expression was assessed on day 1,7,14.Results: Our results verified that hyperoxia caused alveolar and vascular developmental disorders and increased pulmonary vascular permeability, which was consistent with previous findings. In hyperoxia-exposed rat lungs, the expressions of Twist1, Ang1, Tie1, Tie2, and pTie2 were significantly reduced, whereas the expression of Ang2 was significantly increased. Next, we observed a significant down-regulation of the Akt/Foxo1 pathway.Conclusion: In HALI, the pulmonary microvascular permeability was increased, accompanied by changes in Twist1-Tie2 pathway which combined to Angs, and downregulation of Tie1 and Akt/Foxo1 pathway.